Review of neuroprotective potential of natural products against hypoxia-induced neuronal injury - Zhang, Yuman; Yi, Xingyu; Wang, Dingzhong; Kong, Cunlong; Xu, Yan; Xie, Jianping (Frontiers in Pharmacology, 2026)
Neurological disorders such as neurodegenerative diseases (NDDs) and stroke have become a major global health burden. Evidences from several studies suggest that their pathogenesis is related to hypoxia. However, there are certain limitations and adverse effects associated with the current treatments for neurological disorders. Studies have shown that some natural products and their extracts—such as (−)-epigallocatechin-3-gallate, Centella asiatica, ginkgolides, quercetin, berberine, and curcumin, which are the focus of this paper, along with briefly mentioned resveratrol and compounded preparations—have some neuroprotective effects in hypoxia-induced neurological injury. Owing to their favorable safety profile and minimal adverse effects, they have attracted widespread attention. Moreover, their primary mechanisms of action possibly stem from oxidative stress inhibition, neuroinflammation attenuation, and neuronal apoptosis reduction, providing potential approaches for the prevention and treatment of neurological diseases. In this review, we searched the PubMed and Web of Science databases for relevant literature collected over the past 35 years. Overall, we summarized the neuroprotective effects of these natural products against hypoxia-related neurological injury, focusing on the molecular mechanisms and signaling pathways, thereby offering a theoretical basis for further research on the specific neuroprotective mechanisms and drug targets of their observed preventive and therapeutic effects on NDDs, primarily Alzheimer’s disease (AD), Parkinson’s disease (PD), and Huntington’s disease (HD) in this review.